The Intrinsic Elements Analysis on Developing the Character and Theme in Film “Joker” - Oktaviano, Revandy Cekha; Ramiro, Jonathan; Fitriyah (Modality Journal: International Journal of Linguistics and Literature, 2024)
One of the essential components of film is the intrinsic elements. The purpose of the research is to analyse the intrinsic elements of Joker film and the influences of those intrinsic elements on developing the character and the theme of Joker film directed by Todd Phillips. This research used the qualitative method as its research design and the structuralism approach as the tool for analysing the data. The data of this research were taken from dialogues and narrations of Joker's (2019) film script directed by Todd Phillips. Joker is a thriller film that focuses its theme on critiques of society's indifference and the institutions that overlook vulnerable individuals, particularly those struggling with mental health challenges. As a result, this research showed the intrinsic elements of Joker film consisting of plot (exposition, rising action, climax, falling action, and resolution), characters (Arthur Fleck/Joker, Murray Franklin, Penny Fleck, Sophie Dumond), setting (place: Gotham City, The Comedy Club), and point of view which was taken from Arthur’s, theme (mental illness and society neglect, alienation and isolation, identity and transformation, the role of violence in society). Joker film reflects on the importance of empathy and community in addressing the needs of individuals who are suffering. Abstrak Salah satu komponen penting dari sebuah film adalah unsur-unsur intrinsiknya. Tujuan dari penelitian ini adalah untuk menganalisis unsur-unsur intrinsik film Joker dan pengaruh unsur-unsur intrinsik tersebut terhadap pengembangan karakter dan tema film Joker yang disutradarai oleh Todd Phillips. Penelitian ini menggunakan metode kualitatif sebagai desain penelitiannya dan pendekatan strukturalisme sebagai alat untuk menganalisis data. Data penelitian ini diambil dari dialog dan narasi naskah film Joker (2019) yang disutradarai oleh Todd Phillips. Joker adalah film thriller yang memfokuskan temanya pada kritik terhadap ketidakpedulian masyarakat dan lembaga-lembaga yang mengabaikan individu-individu yang rentan, terutama mereka yang berjuang dengan tantangan kesehatan mental. Hasil penelitian ini menunjukkan unsur intrinsik film Joker yang terdiri dari alur (eksposisi, rising action, klimaks, dropping action, dan resolusi), karakter (Arthur Fleck/Joker, Murray Franklin, Penny Fleck, Sophie Dumond), latar (tempat: Gotham City, The Comedy Club), dan sudut pandang yang diambil dari tema Arthur (penyakit mental dan pengabaian masyarakat, alienasi dan isolasi, identitas dan transformasi, peran kekerasan dalam masyarakat). Dalam film Joker merefleksikan pentingnya empati dan komunitas dalam mengatasi kebutuhan individu yang sedang menderita.Kata kunci: unsur intrinsik, deskriptif kualitatif, film, joker.